Validation of implicit expectations on mobile applications - Andriano, Natalia Valeria (2020)
The increasing amount of active software users together with the emergence of free access to multi-screen devices (being mobile phone the leaders in this area), have started to cause a growing phenomenon on the user expectations for every software product (no matter what it is about). Identifying these expectations will benefit the development of products (for example, in estimating more accurately the size and cost of a product), while will improve the reception of it by end users. This research verifies and validates a list of implicit items, deemed common to many products, against the top 10 worldwide most used apps.